Zeolitic imidazolate framework‐8 reinforced hollow‐fiber liquid‐phase microextraction of free urinary biomarkers of whole grain intake followed by CE analysis. Issue 14 (4th June 2020) - Fang, Zhonghui; Gong, Jiacheng; Jing, Xiaofeng; Wang, Tingting; Ye, Jiannong; Chu, Qingcui; Huang, Dongping
Abstract: The whole grain intake is closely associated with human health. In this work, three‐phase dynamic hollow‐fiber liquid‐phase microextraction reinforced with 0.10 mg/mL 30 nm zeolitic imidazolate framework‐8 nanoparticles was introduced for purification and enrichment of free urinary metabolite biomarkers of whole grain intake. Eight milliliters of HCl (pH 3.00) and 8 μL of 300 mM NaOH solutions were used as the donor and acceptor phases, respectively. The temperature and stirring rate were kept at 25℃ and 500 rpm, and the extraction time was 40 min. The extraction process required no further desorption, and the resultant extract was directly used for electrophoretic analysis without derivatization. Based on the synergistic effect of hollow‐fiber liquid‐phase microextraction and the electrophoretic stacking, the enrichment factors of 3, 5‐dihydroxybenzoic acid and 3‐(3, 5‐dihydroxyphenyl)‐1‐propionic acid reached 1018–1034 times, and their limits of detection achieved 0.33–0.67 ng/mL (S/N = 3) in urine matrix. The developed method has been successfully used for urine analysis, and the sample recovery data were in the range of 97.0–103.5%. This developed method provided an attractive alternative for the determination of urinary metabolite biomarkers of whole grain intake due to its sensitive, fast, low‐cost, and environmental‐friendly features.